Bio‐Inspired Evaporation Through Plasmonic Film of Nanoparticles at the Air–Water Interface. Issue 16 (12th May 2014) - Wang, Zhenhui; Liu, Yanming; Tao, Peng; Shen, Qingchen; Yi, Nan; Zhang, Fangyu; Liu, Quanlong; Song, Chengyi; Zhang, Di; Shang, Wen; Deng, Tao
<x xml:space="preserve">Abstract</x> Plasmonic gold nanoparticles self‐assembled at the air–water interface to produce an evaporative surface with local control inspired by skins and plant leaves. Fast and efficient evaporation is realized due to the instant and localized plasmonic heating at the evaporative surface. The bio‐inspired evaporation process provides an alternative promising approach for evaporation, and has potential applications in sterilization, distillation, and heat transfer. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>